The Italian credit and financial system : report by the commission appointed by the minister of the treasury - Monti,Mario; Cesarini,Francesco; Scognamiglio,Carlo (Rome : Banca Nazionale del lavoro, 1983)
The evolution of Italian banking,the problems faced by that system and ideas being elaborated in a debate on the future of international credit and finance
obn 24/01/2019
Loans
Keywords: Credit-Italy; Financial institutions-Italy; Credit